Emprego da Microscopia Eletroquímica de Varredura SECM na investigação de processos interfaciais visando o desenvolvimento de sensores químicos - Macena, Cleidivan Silva (2017)
The present work demonstrated the potential of Scanning Electrochemical Microscopy (SECM) in the understanding of enzymatic systems using the enzymes glucose oxidase (GOx) and the peroxidase of strong root (HRP) as recognition model. In addition, it evaluated different platforms, such as: Graphene (Gr) and Carbon Nanotubes (CNTs) in the response of enzymatic systems through approximation curves and images. In this sense, the reactivity of the GOx and HRP enzymes was evaluated in the generator / collector mode on an insulating platform. In addition, the HRP was studied comparatively on graphene platform Gr, CNTs and on conductive surface. The use of the SECM technique in the investigation of these systems showed its applicability in the investigation of reactions catalyzed by enzymes and also showed that CNTs were the best platform for immobilization of HRP. In addition, it showed the application of SECM in enzymatic systems for the selective determination of compounds isomers: catechol and hydroquinone.